An Experimental Study: Benefits of Digoxin on Hepatotoxicity Induced by Methotrexate Treatment - Banu Taskin (Hindawi Limited, 2021)
Purpose. The aim of the study is to examine the possible therapeutic effects of a known cardiac glycoside, digoxin, on a rat model of MTX-induced hepatotoxicity. Methods. The study was conducted on twenty-four male rats. While eighteen rats received a single dose of 20 mg/kg MTX to obtain an injured liver model, six rats constituted the control group. Also, the eighteen liver toxicity model created rats were equally divided into two groups, one of which received digoxin 0.1 mg/kg/day digoxin (Group 1) and the other group (Group 2) was given saline (% 0.9NaCl) with a dose of 1 ml/kg/day for ten days. Following the trial, the rats were sacrificed to harvest blood and liver tissue samples to determine blood and tissue MDA, serum ALT, plasma TNF-α, TGF-β, IL-6, IL-1-Beta, and PTX3 levels. Results. MTX’s structural and functional hepatotoxicity was observable and evidenced by relatively worse histopathological scores and increased biochemical marker levels. Digoxin treatment significantly reduced the liver enzyme ALT, plasma TNF-α, TGF-β, PTX3, and MDA levels and decreased histological changes in the liver tissue with MTX-induced hepatotoxicity in the rat model. Conclusion. We suggest that digoxin has an anti-inflammatory and antihepatotoxic effect on the MTX-induced liver injury model.